Solving Method of H-infinity Model Matching Based on the Theory of the Model Reduction - Li Linzhi; Cao Xinjun (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
People used to solve high-order  model matching based on  control theory, it is too difficult. In this paper, we use model reduction theory to solve high-order  model matching problem, A new method to solve  model matching problem based on the theory of the model reduction is proposed． The simulation results show that the method has better applicability and can get the expected performance．